Carbon Reserve Potential of Coffee Agroforestry Standing in Protected Forest Area, Paya Tungel Village, Central Aceh Regency - Subhan Subhan; Ashabul Anhar; Anna Farida; Ali M Muslih; Putri Maizenia; Ghina Erida; Nil Fazly Nik Roseli; Siti Maimunah (Politeknik Pertanian Negeri Samarinda, 2025)
Forests are able to absorb large amounts of carbon. There are various kinds of forests in Indonesia, one of which is protected forest. Protected forest is a forest area that has a main function as a protection of life support systems and must be protected and has been determined by the government or community groups. The purpose of this study was to determine the potential of carbon stocks in agroforestry stands in Protected Forests in Paya Tungel Village, Central Aceh Regency. The results showed that the most dominant vegetation species composition at the seedling, sapling and pole level was coffee (Coffea arabica) while the tree level was Lamtoro (Leucaena leucocephala). The amount of carbon stock in the agroforestry forest is 612.08 tons Ha-1